Spontaneous Bladder Rupture in a Catatonic Schizophrenia Patient - Miyakoshi, Megumi; Arai, Takayuki; Kurose, Shin; Kaji, Masataka; Nakane, Jun; Onaya, Mitsumoto; Koreki, Akihiro (Case Reports in Psychiatry, 2023)
Catatonia is a psychiatric emergency in schizophrenia that often leads to excessive activation of the sympathetic nervous system. Urinary retention in catatonia is often underestimated but has potentially detrimental consequences. Herein, we present the case of a woman in her 40s with schizophrenia treated for catatonia during a relapse. When treated as an inpatient, the patient suddenly complained of severe abdominal pain. Computed tomography revealed a spontaneous rupture of the posterior wall of the bladder, requiring emergency repair surgery in the urology department. The patient was readmitted to our hospital following surgery and ultimately discharged 1 month later. Bladder rupture is life-threatening, and delayed diagnosis and treatment can be fatal. This case report serves as a warning that psychiatrists should not overlook urinary retention in patients with catatonia and should consider bladder rupture in the differential diagnosis when these patients have abdominal pain.